2022
DOI: 10.15408/tazkiya.v10i2.26341
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from Long COVID: How College Students Thrive During Lockdown

Abstract: The Long COVID-19 Syndrome affected the lives of college students on lockdown for almost two years (2020-202), is the focus of this paper. Specifically, this study examined their stress, anxiety, depression levels, and psychosocial factors (socioeconomic status, adverse childhood experiences, and perceived social support) were related to these mental health issues. The impact of the Long COVID-19 on the students’ well- being and their coping mechanisms were explored. Using a cross- sectional survey research de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…In the United States, 31.9% of school students experience anxiety disorders (The National Institute of Mental Health, 2018). Research has shown that depression and anxiety are among the most common mental health conditions experienced by adolescents (Dandala & Hodambia, 2021;Jia & Vu, 2023;Cabacungan et al, 2022). These conditions can have a significant impact on adolescents' overall well-being, including cognitive functioning, social skills and emotional development (Astutik & Dewi, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, 31.9% of school students experience anxiety disorders (The National Institute of Mental Health, 2018). Research has shown that depression and anxiety are among the most common mental health conditions experienced by adolescents (Dandala & Hodambia, 2021;Jia & Vu, 2023;Cabacungan et al, 2022). These conditions can have a significant impact on adolescents' overall well-being, including cognitive functioning, social skills and emotional development (Astutik & Dewi, 2022).…”
Section: Introductionmentioning
confidence: 99%